1996
DOI: 10.1111/j.1460-9568.1996.tb01314.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BDNF and NT‐4/5 on Striatonigral Neuropeptides or Nigral GABA Neurons In Vivo

Abstract: Supranigral infusions of the TrkB-receptor-preferring neurotrophins BDNF or NT-4/5 augment locomotor behaviours, pars compacta firing rates and striatal dopamine metabolism. However these actions of BDNF or NT-4/5 may involve other neurotransmitter systems in addition to dopamine neurons in the substantia nigra. We thus investigated the effects of 2-week supranigral infusions of BDNF or NT-4/5 on rat peptidergic striatonigral neurons and nigral GABAergic neurons. Radioimmunoassay revealed that BDNF and NT-4/5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 58 publications
0
35
0
1
Order By: Relevance
“…Other neurotrophic factors (e.g. neurotrophin 3, brain derived neurotrophic factor, neurotrophin 4/5) are also known to modulate neurotransmitter release and synaptic function (Arenas et al, 1996;He et al, 2000;Lessmann et al, 1994;Lessmann and Heumann, 1998;Li et al, 1998;Liou and Fu, 1997;Lohof et al, 1993). The role of GDNF and NRTN in synaptic transmission within the ENS will need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Other neurotrophic factors (e.g. neurotrophin 3, brain derived neurotrophic factor, neurotrophin 4/5) are also known to modulate neurotransmitter release and synaptic function (Arenas et al, 1996;He et al, 2000;Lessmann et al, 1994;Lessmann and Heumann, 1998;Li et al, 1998;Liou and Fu, 1997;Lohof et al, 1993). The role of GDNF and NRTN in synaptic transmission within the ENS will need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF has been demonstrated to directly rescue CNS GABA neurons and stimulate GABA neurotransmitter synthesis. [29][30][31][32] Exogenous BDNF has been seen to have a direct positive effect on both uninjured 33 and injured 34 serotonergic neurons in the brainstem, increasing 5HT synthesis and promoting regeneration of 5HT-axons, respectively. Transplants of BDNF-secreting cells in the subarachnoid space after nerve injury has been shown to restore the endogenous GABA system within 1 week after grafting.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,[37][38][39][40] Whether such loss of GABA synthesis is due to excitotoxic cell death of GABA interneurons or temporary or permanent alterations in the neurotransmitter's synthesis, is not known, but neurotrophins such as BDNF may act directly to intervene in cell death and/or regulate GAD enzyme activity, as has been seen with BDNF and other GABA cells. [29][30][31][32] Assigning only a antinociceptive function for endogenous BDNF in neuropathy is difficult. Neurotrophic factors such as BDNF, and NT-3 play a significant role in the development, and perhaps maintenance, of the sensory neurons responsive to temperature and tactile pain, evidenced in neurotrophin-knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of BDNF in cortical interneuron development is not without debate. Other studies have suggested that disruption of BDNF signalling leads to downregulation of CB and other neuropeptides expressed in interneurons [91,123,124]. This would cast some doubt as to whether the reduction of interneuron numbers in the absence of TrkB reflects an actual defect in migration or simply a reduction of cell markers.…”
Section: Tangential and Radial Migratory Routesmentioning
confidence: 94%